Efektivitas Program Peserta Bantuan Iuran (PBI) di Kota Medan dalam Menurunkan Angka Rumah Tangga Tidak Terlindungi Jaminan Kesehatan - Zakia Aulia; Waizul Qarni; Rahmi Syahriza (Jurnal Riset Akuntansi, 2025)
The Premium Assistance Participant Program (PBI) is a government health insurance protection scheme provided through the National Health Insurance (JKN) for poor and underprivileged communities. In Medan City, several households remain uncovered by health insurance, indicating the need to evaluate the effectiveness of the PBI program in supporting the achievement of universal health coverage. This study aims to analyze the effectiveness of the PBI Program in reducing the number of households without health insurance coverage in Medan City. The study employed a qualitative approach with a descriptive evaluative design. Data were collected through interviews, observations, documentation, and secondary data from the Medan City Health Office, BPJS Kesehatan, and related institutions. The analysis focused on PBI participant coverage, accuracy of beneficiary data, utilization of health services, and changes in the number of uninsured households. The results indicate that the PBI Program has contributed to reducing the number of households without health insurance coverage in Medan City. However, several challenges remain, including inaccurate beneficiary data, limited program socialization, and administrative issues that prevent some eligible poor communities from being registered as PBI participants. The study concludes that the PBI Program is relatively effective in expanding health insurance protection, but improvements are still required in data management, information dissemination, and inter-agency coordination to optimize coverage and service quality.